Metaphors of coming out in Polish: A cognitive linguistic approach - Dyrmo Tomasz (Topics in Linguistics, 2023)
The following qualitative study focuses on the metaphors of coming out in the Polish language. Native Polish speakers were asked to define coming out and then describe their coming out experiences. Data from 94 participants were analysed. The results from the analysis show that, consistently with the previous study on English data (Dyrmo, 2022b), coming out metaphors are based on several different conceptual structures and meaning foci, for example the image schema of FORCE and CONTAINER, the concept of openness and visibility, the domain of MOVEMENT and TRANSFER, the frame of SHARING AN OBJECT and two discursively oriented metaphorical scenarios: COMING OUT IS MAKING YOUR ORIENTATION VISIBLE TO OTHERS and COMING OUT IS SHIFTING A HEAVY OBJECT OFF YOUR SHOULDERS. The present analysis lays ground for further multimodal analyses of coming out metaphors.